Beliefs About Parent Participation in School Activities in Rural and Urban Areas: Validation of a Scale in Mexico - Echeverría-Castro, Sonia Beatriz; Sandoval-Domínguez, Ricardo; Sotelo-Castillo, Mirsha Alicia; Barrera-Hernández, Laura Fernanda; Ramos-Estrada, Dora Yolanda (Frontiers in Psychology, 2020)
The objective of this study was to test a measurement and invariance model for a scale of beliefs about parent participation in school education for children residing in both rural and urban areas. The questionnaire was answered by 2,576 parents, 52% from urban areas, 48% from rural; also an exploratory confirmatory multigroup analysis was performed to identify invariance. The final version of the instrument consisted of two factors with three items each, showing a goodness of fit, in addition to adequate indices. The invariance analyses indicated that both samples were equivalent in structure and factorial weight. The comparative fit index was greater than 0.95 for each model, and when compared with the restrictive model, the differences were less than 0.01; therefore, the instrument is considered applicable.